Prenatal diagnosis of congenital harlequin ichthyosis with 2D, 3D, and 4D ultrasonography - (:unkn) unknown (I R O G CANADA, INC, 2011)
Harlequin fetus is a rare and mostly fatal form of congenital ichthyosis that can be diagnosed by fetal skin biopsy in patients with a family history of the disease. More recently DNA analysis of amniocentesis and chorion villus sampling materials have also been utilized. We report a case of prenatally diagnosed congenital ichthyosis with no previous family history. Diagnosis was mainly achieved by 3D and 4D ultrasonography findings such as diffuse scaling of the skin, digital contractures, flattened rudimentary external ear, nasal hypoplasia, everted eyelids, typical fish mouth appearance, macroglossia, and persistently open fetal mouth.
Keywords: 3D ultrasound; Harlequin ichthyosis; Prenatal diagnosis; 3-DIMENSIONAL SONOGRAPHIC FINDINGS; ULTRASOUND; FETUS